Low‐carbon energy, sustainable development, and justice: Towards a just energy transition for the society and the environment. (3rd May 2021) - Siciliano, Giuseppina; Wallbott, Linda; Urban, Frauke; Dang, Anh Nguyen; Lederer, Markus
Abstract: Governments and civil society are increasingly aware that the decarbonization of energy systems needs to be aligned with justice principles of recognition, distribution, and process. This paper establishes a conceptual linkage between "sustainable development", "low‐carbon energy transitions" and "energy justice" and examines social priorities to address peoples' competing priorities associated with low‐carbon energy interventions. By analyzing a renewable energy project in Vietnam as a case study, the paper shows that linking social priorities to energy justice provides a useful contribution for energy policy makers toward a better understanding of the multidimensional and complex aspects of low‐carbon energy transitions, and how different segments of society prioritize and perceive them for the achievement of socially just energy decisions.